Time allocation to energy resource collection in rural Ethiopia: Gender-disaggregated household responses to changes in firewood availability - Scheurlen, Elena (International Food Policy Research Institute, 2015)
This paper presents evidence on rural Ethiopian households’ time allocation to different activities, especially fuel collection work, and examines the effect of changes in the availability of firewood resources on households’ time allocation to fuel collection and on- and off-farm income generation. Based on firsthand insights from focus group discussions conducted with farmers in three rural villages of Ethiopia and data from an IFPRI-CIMMYT (International Food Policy Research Institute/International Maize and Wheat Improvement Center) household survey implemented by the Association of Ethiopian Microfinance Institutions, the results show that women are involved in more time-consuming and simultaneous work activities than men and hold the primary responsibility for fuel collection